A Brief History of Medical Anatomy - Olegário, Raphael Lopes; Lopes, Bruno Sousa; Strini, Paulinne Junqueira Silva Andresen; Strini, Polyanne Junqueira Silva Andresen; de Melo, Lídia Mara Aguiar Bezerra (Revista de Medicina e Saúde de Brasília, 2019)
The focus on anatomy in the ancient world began as a way to determine the nature of the soul. It has been characterized, over time, by a continually developing understanding of the functions of organs and structures in the body. Progress today is centered in the development, evolution and function of anatomical features. The history of anatomy includes not only professors and the support of their institutions but also medical and health students. Some anatomists use their dissection skills in a traditionally artistic way and render their specimens into lasting work of art. The aim of this article has been to clarify the historical development process of the human anatomy over the years.